War words : language, history, and the disciplining of English - Clark, Urszula (Elsevier, 2001)
Debates about the nature of literacy and literacy practices have been conducted extensively in the last fifteen years or so. The fact that both previous and current British governments have effectively suppressed any real debate makes the publication of this book both timely and important. Here, Urszula Clark stresses the underlying ideological character of such debates and shows that they have deep historical roots. She also makes the point that issues regarding the relationship between language and identity, especially national identity, become sharply focused at times of crisis in that identity. By undertaking a comparison with other major English-speaking countries, most notably Australia, New Zealand and the USA, Clark shows how these times of crisis reverberate around the globe.